A profile of children living in shelters: Parents' perspectives on their children's health and factors that influence it. - Robeson, Paula Marie. (University of Ottawa (Canada), 2002)
Objective. To describe a profile of school-aged children (5--14 years) living in shelters in Ottawa including risk and protective factors commonly associated with health related outcomes in children. Design. A descriptive research study using a pre-tested survey questionnaire designed by the researcher, based on the literature, and guided by a resilience framework. Setting. Three emergency family shelters in Ottawa. Participants. 34 parents with 61 children (aged 5 to 14 years) living at the shelters. Conclusions. Risk and protective factors at the individual, family, and community levels are presented. Protective factors of children living in shelters should be recognised, strengthened, and maintained. Efforts to minimise the risk factors should be undertaken. Implications for nursing practice and research are discussed. (Abstract shortened by UMI.)
Keywords: Health Sciences, Nursing.